Perceived Service Quality and Behavioural Intention: A Survey of Corporate Hospital’s Patients: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of this paper is to investigate the relation between perceived service quality and Behavioural intention in corporate hospitals in Delhi-NCR. Methodology– We adopted the three items scale developed by Choi et al. (2004) to measure the behavioural intention. Additionally, we measured the perceived service quality (tangibility, reliability, responsiveness, assurance, and empathy), using the items from Babakus and Mangold (1992) research. We framed a modified structured questionnaire to collect responses on perceived service quality and behavioural intention. We used the structural equation modeling technique to investigate the impact of perceived service quality dimension on behavioural intention in corporate hospital in Delhi-NCR.Findings – The findings suggest that perceived tangibility, responsiveness, assurance and empathy positive significantly influence the behavioural intention of patients in corporate hospitals but reliability does not significantly influence the behavioural intention.